1209-1191 Washington Street, ca. 1870 - Unknown (Tufts Archival Research Center, 2005)
Elevated view west-northwest of (left to right) 1209-1191 Washington Street, located between Union Park Street to the northeast and Pelham Street to the southwest. Signage adorns the facades of the buildings, which face southeast. The steeple of the South Congregational Church, located on Union Park Street, is visible to the immediate right of 1191-1209 Washington Street. A horse-drawn vehicle is located on Union Park Street, and pedestrians are included in the photograph. 2 1/4 x 3 1/8, 2 1/2 x 4 1/8 overall Cartes-de-visite